Targeting synthesis of the Chromosome Replication Initiator Protein DnaA by antisense PNA-peptide conjugates in Escherichia coli - Campion, Christopher; Charbon, Godefroid; Nielsen, Peter E.; Løbner-Olesen, Anders (Frontiers in Antibiotics, 2024)
Initiation of chromosome replication is an essential stage of the bacterial cell cycle that is controlled by the DnaA protein. With the ultimate aim of developing novel antimicrobials, we have targeted initiation of DNA replication, using antisense peptide nucleic acids (PNAs), directed against DnaA translation. A series of anti-DnaA PNA conjugated to lysine rich bacterial penetrating peptides (PNA-BPPs) were designed to block DnaA translation. These anti-DnaA PNA-BPPs inhibited growth of wild-type E. coli cells at low micromolar concentrations, and cells exposed to anti-DnaA PNA-BPPs, exhibited characteristic hallmarks of chromosome replication inhibition. These results present one of very few compounds successfully targeting initiation of chromosome replication, an essential step in the bacterial cell cycle.